The Difference in the Effects of Mini Squat on Balance Pad and Lunge Stabilization Focus on Improving Stabilization - Astrid Komala Dewi; Catherine Hermawan Salim; Ribka Sabarina Panjaitan; Ria Efkelin (Jurnal EduHealth, 2025)
This study aimed to determine the differences in the effects of Mini Squat on Balance Pad exercise and Lunge with Focused Stabilization exercise on improving stabilization. The sample consisted of 40 participants, selected using a random sampling technique using a provided questionnaire. The sample was divided into two treatment groups: Treatment Group I, consisting of 20 participants, received the Mini Squat on Balance Pad exercise, and Treatment Group II, consisting of 20 participants, received the Lunge with Focused Stabilization exercise. Method: This study used a quasi-experimental pre-post test design. Statistical analysis used the Related T-Test and Independent T-Test. The results of the homogeneity test for the treatment groups before exercise showed a p-value of 0.008. The Related T-Test results for Treatment Group I showed a p-value of 0.001, and for Treatment Group II, a p-value of 0.001, indicating that the exercises given to each group had an effect on improving stabilization. The results of the Independent T-Test showed a p-value of 0.001, indicating a highly significant effect between treatment group I and treatment group II. It can be concluded that there is a highly significant difference in the effects of the Mini Squat on Balance Pad exercise and the Lunge with Focused Stabilization exercise on improving stabilization. This study recommends applying the training method with the correct procedure, and performing it over a period of more than one month. Improved stabilization results will be better if performed over a period of 2-3 months. It is also hoped that factors that could influence the research results can be minimized to achieve optimal results.